Reservation-based distributed medium access in wireless collision channels - Menache, Ishai; Shimkin, Nahum (Telecommunication systems, 2011)
We consider an uplink wireless collision channel, shared by multiple mobile users. The medium access protocol incorporates channel reservation that relies on RTS (request-to-send) and CTS (clear-to-send) control packets. Consequently, collisions are reduced to the relatively short periods where mobiles request channel use. In our model, users individually schedule their channel requests, and the objective of each user is to minimize its own power investment subject to a minimum-throughput demand. Our analysis reveals that for feasible throughput demands, there exist exactly two Nash equilibrium points in stationary strategies, with one superior to the other uniformly over all users. We then show how this better equilibrium point can be obtained through distributed best-response mechanisms. Finally, we quantify and discuss the effect of the relative length of data and control periods on capacity, power and delay.